Effects of Stepwise Microwave Synergistic Process Water Recirculation During Hydrothermal Carbonization on Properties of Wheat Straw - Zhang, Xinyan; Qin, Qingyu; Liu, Xian; Wang, Wenlong (Frontiers in Energy Research, 2022)
In this study, wheat straw (WS) was treated using two-step synergistic techniques, which were process water recirculation (PWR) during hydrothermal carbonization (HTC) and microwave energy activation (MEA). The physicochemical properties of solid and liquid products during the process of HTC PWR were characterized. The temperature-rising properties, yields, and fuel properties of hydrochar after MEA were explored. Then the optimal technique conditions were explored. When HTC PWR was twice, the carbon content (55.59%) and higher heating value (21.72 MJ/kg) were the highest, the ash content (1.93%) and the O/C and H/C ratios were the lowest. When HTC PWR was three times, the fixed carbon content, mass yield, and energy yield were the highest: 18.53%, 58.25%, and 71.84%, respectively. Much more carbon microspheres and pores appeared on the surface of hydrochar after PWR, which could improve the fuel characteristics and mass yield. After HTC PWR, the concentration of organic acids and HMF in liquid by-products increased, which was conducive to the increase of carbon content and mass yield. The best effect was HTC PWR twice or three times. With the increase of microwave power or the extension of microwave activation duration, the temperature-rising properties of hydrochar significantly increased, and the mass and energy yields decreased. The volatile contents of hydrochar decreased and their fixed carbon contents and HHV increased with the increase of microwave power. The properties of hydrochar could be improved when MEA was 900W or 1000W for 4 min. Therefore, MEA had significant effects on the properties of hydrochar after different PWR conditions.